SIFAT PAPAN WOL KAYU DARI 10 JENIS KAYU NUSA TENGGARA BARAT - l M Sulastiningsih; Rodjak Memed; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1991)
The results of laboratory   test of wood-wool  board properties made fram ten wood species obtained from Nusa  Tenggara province are reported in   this paper.   The properties tested were board  density,   moisture  content,  thickness  reduction  due  Io compression   and  benJing strengih.The Study  revealed   that the average yield of  wood-wool was 423,6 kg per cubic  meter of  log input.   The wood-wool   of  Anthoceplus cadamba  Miq.  and Anthocephallus  sp.  must  be soaked  in cold  water for  24 houn   prior  to manufacturing   of wood-wool   board,  whereas she other species did not require soaking.   The physical  and mechanical  properties  of wood-wool  board from  nine wood  species  mineralized  with CaCl2 solution  were in conformity   with the  DIN  1101 standard.  However, only  three wood  species   mineralized   with Ca   (OH)2  suspension met  the standard  requirement.